2009
DOI: 10.1007/s00248-009-9539-3
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Antimicrobial Resistance of Gram-Negative Bacteria from Natural Oligotrophic Lakes Under Distinct Anthropogenic Influence in a Tropical Region

Abstract: The aim of this study was to evaluate the resistance to ten antimicrobial agents and the presence of bla ( TEM1 ) gene of Gram-negative bacteria isolated from three natural oligotrophic lakes with varying degrees of anthropogenic influence. A total of 272 indigenous bacteria were recovered on eosin methylene blue medium; they were characterized for antimicrobial resistance and identified taxonomically by homology search and phylogenetic comparisons. Based on 16S ribosomal RNA sequences analysis, 97% of the iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
39
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 53 publications
7
39
0
1
Order By: Relevance
“…This result is in agreement with previous studies of bacterial diversity in freshwater, which have reported the occurrence of these phyla (Hiorns et al 1997, Berg et al 2009). Moreover, the dominance of Proteobacteria and the relatively small numbers of Bacteroidetes and Deinococcus-Thermus have also been reported in previous studies (Lemke et al 2009, Pontes et al 2009). Enterobacter, Moraxella, Staphylococcus and Acinetobacter have also been detected in lentic environments (Berg et al 2009, Lemke et al 2009).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…This result is in agreement with previous studies of bacterial diversity in freshwater, which have reported the occurrence of these phyla (Hiorns et al 1997, Berg et al 2009). Moreover, the dominance of Proteobacteria and the relatively small numbers of Bacteroidetes and Deinococcus-Thermus have also been reported in previous studies (Lemke et al 2009, Pontes et al 2009). Enterobacter, Moraxella, Staphylococcus and Acinetobacter have also been detected in lentic environments (Berg et al 2009, Lemke et al 2009).…”
Section: Discussionsupporting
confidence: 77%
“…The DNA was purified as previously described by Dramsi et al (1995). The complete 16S rRNA gene was amplified by touchdown PCR according to Pontes et al (2009), using the conserved primer set PA (5'-TCC TGG CTC AGA TTG AAC GC-3'), modified from Kuske et al (1997), and U2 (5'-ATC GGY TAC CTT GTT ACG ACT TC-3'), described by Lu et al (2000). …”
mentioning
confidence: 99%
“…Due to the extensive human and veterinary utilization and the potentials to cause the selective proliferation of antibiotic resistant bacteria, antibiotics have raised increasing concerns recently (Pontes et al, 2009;Wilkinson et al, 2016). Antibiotics, including their parent compounds and transformation products, are being continuously discharged into the environment during manufacturing, consumption and disposal (Daughton and Ternes, 1999;Lin et al, 2010;Sharma et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies reported that the bla TEM-1 gene was detected in most of the Gram-negative isolates resistant to ampicillin recovered from lakes in Brazil or from wastewater treatment plants in China (24,40). Furthermore, several studies identified extended-spectrum ␤-lactamases (ESBLs) from water samples.…”
mentioning
confidence: 99%